2016
DOI: 10.1038/hgv.2016.22
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic developmental defect evaluated by celiac artery angiography in a patient with MODY5

Abstract: The hepatocyte nuclear factor 1β gene (HNF1B) is responsible for maturity-onset diabetes of the young type 5 (MODY5), which is characterized by early-onset diabetes mellitus and urogenital malformations. HNF1B is expressed during visceral endoderm formation. We identified a disruption of the great pancreatic artery in a patient with MODY5 with no pancreatic body or tail. Our finding supports the significance of HNF1B in the development of the pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Pancreatic abnormalities in MODY5 were mainly dysplasia. Ventral pancreatic dysplasia was the most prominent, because HNF1B was related to ventral pancreatic development, its mutation could cause pancreatic dysplasia (19)(20)(21). It was also reported that patients might have pancreas divisum, intraductal papillary mucinous tumo, yet these manifestations were extremely rare (6).…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic abnormalities in MODY5 were mainly dysplasia. Ventral pancreatic dysplasia was the most prominent, because HNF1B was related to ventral pancreatic development, its mutation could cause pancreatic dysplasia (19)(20)(21). It was also reported that patients might have pancreas divisum, intraductal papillary mucinous tumo, yet these manifestations were extremely rare (6).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, no other illnesses or health problems were found. To elucidate the various clinical presentations and characteristics of Chr17 deletion, we compared the clinical manifestations in our proband and previously reported patients with a similar deletion region (34,437.475-36,424,950) in Chr17q12 [7][8][9][10][11][12][13][14][15] (Fig. 2, Table 1).…”
Section: Case Presentationmentioning
confidence: 99%
“…In humans, mutations in the HNF1B gene result in renal cysts, diabetes syndrome and noninsulin-dependent diabetes mellitus. Some individuals with HNF1B mutations display pancreatic exocrine dysfunction, pancreatic hypoplasia, and, in some cases, complete absence of the pancreatic body and tail suggesting specific loss of dorsal pancreatic development (13,71). HNF6 (Hepatic Nuclear Factor 6; also known as ONECUT1 or OC-1) binds DNA to elicit transcription of genes that are important throughout endodermal development.…”
Section: Hepatocyte Nuclear Factorsmentioning
confidence: 99%